ANALISIS KADAR ETANOL HASIL FERMENTASI RAGI ROTI PADA TEPUNG UMBI GADUNG (DIOSCOREA HISPIDA DENNST) TERHADAP KADAR ETANOL - Hartono, .; Halifah, Pagarra (Fakultas MIPA UNM, 2011)
The research aims to know the long influence of fermentation with bread yeast in Dioscorea hispida flavor to ethanol production. This experiment research was doing in Balai Besar Labolatorium Departemen Kesehatan RI (BBLDKRI), Makassar. The sample of the research was 250 g in every sample of Dioscorea hispida flavor. It had done by chemical by use HCl which boiling in 120°C. This research used 4 M HCl which repeat in 3 times. The result of hydrolysis was 48 hours, 96 hours, and 144 hours. This research used free variable that is the long time of fermentation and variable that was the ethanol value of Dioscorea hispida that had fermented. This research used random complete planning and picnometer was used to know the ethanol value and match it at the kind of the weight table. The result of data analysis showed that the ethanol value in Dioscorea hispida flavor which fermented is 0.0% control); 0.5% (48 hours); 1.1% (96 hours), and 3.6 % (144 hours). The result of this research showed that there was the long influence of the fermentation to the ethanol value in Dioscorea hispida flavor fermentation and after doing the inferential technique analysis and between control and treatment proved that the last fermentation is obvious different with the ethanol value. So, can be concluded that longer time that used in fermentation (144 Hours), higher the ethanol value (3.6 %) in the (Dioscorea hispida).